A monodisperse porous molybdenum powder and its preparation method and application
By using low-temperature reduction of sheet-like molybdenum dioxide and ball milling treatment of potassium bicarbonate during the preparation of molybdenum powder, combined with the effect of liquid potassium hydroxide, the problems of uneven particle size, agglomeration and uneven pores in the preparation of traditional molybdenum powder were solved, and monodispersed porous molybdenum powder with high dispersion and high binding strength were prepared.
Patent Information
- Application Number
- CN202510072178.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2045-01-17
AI Technical Summary
In the traditional molybdenum powder preparation method, there are problems such as uneven particle size distribution, agglomeration phenomenon, and uneven pores, which affect its processing and binding properties as alloy raw materials or coating materials.
The reduction treatment of sheet-like molybdenum dioxide at 750°C to 800°C was performed to obtain a plane-dispersed molybdenum powder, and then mixed with potassium bicarbonate to grind it, and reacted at a low temperature at the decomposition temperature of potassium bicarbonate, and then heated to 1000°C to 1150°C for the second insulation treatment, and liquid potassium hydroxide was used to promote the dispersion of molybdenum powder and the uniform distribution of pores.
Monodispersed porous molybdenum powder with uniform particle size, high dispersion and uniform pore distribution was prepared, which increased the bonding strength between it as a coating material and the ceramic matrix, reaching 34.2MPa~40.3MPa.
Smart Images

Figure CN119457104B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of molybdenum powder preparation, and more specifically to a monodisperse porous molybdenum powder and a preparation method and application thereof. Background Art
[0002] Alloys prepared by traditional powder metallurgy have the advantages of high strength and good thermal conductivity. At the same time, with the improvement of service conditions, higher requirements are placed on the functionality of alloy materials. Powder metallurgy porous materials made by pressing and sintering metal alloy powders have the characteristics of large specific surface area, excellent permeability, weldability and good machinability.
[0003] The traditional method of preparing molybdenum powder will inevitably lead to uneven particle size distribution, and agglomeration will occur to reduce the surface free energy of the powder. When there are coarse and aggregated particles in the molybdenum powder, the loose density of the molybdenum powder will be reduced, making it difficult to press and form, and coarse grains will be formed after sintering, which will affect the processing performance of molybdenum powder as a raw material to prepare molybdenum alloys or the bonding performance of molybdenum powder with the substrate when used as a coating.
[0004] In the prior art, researchers have mainly solved the problem of molybdenum powder agglomeration by means of particle size homogenization and powder pulverization. However, particle size homogenization has strict requirements on gas partial pressure and is difficult to accurately control. The pulverization technology has problems such as insufficient pulverization and the need for complex multi-pass processing. The traditional method of using urea and other pore-forming agents to directly form pores to obtain porous molybdenum powder has problems such as uneven pore distribution and uneven sizes, and the powder also has agglomeration. Summary of the invention
[0005] In view of the above problems, the present invention provides a monodisperse porous molybdenum powder and a preparation method and application thereof. The present invention is easy to operate, does not require crushing treatment, and the prepared molybdenum powder has high dispersibility and uniform pore distribution under the action of potassium bicarbonate.
[0006] The first object of the present invention is to provide a method for preparing monodisperse porous molybdenum powder, comprising the following steps:
[0007] Under a reducing atmosphere, the lamellar molybdenum dioxide is subjected to a reduction treatment at 750°C to 800°C to obtain molybdenum powder; the molybdenum dioxide is converted into molybdenum powder by the reduction treatment. The reason why the present invention selects lamellar molybdenum dioxide is that the molybdenum powder obtained after the reduction treatment at 750°C to 800°C is planar dispersion. If other morphologies are selected, there will be a problem of easy agglomeration and stacking. For example, the temperature of the reduction treatment is 750°C, 760°C, 770°C, 780°C, 790°C, 800°C, etc., but it is not limited to the listed values, and other values not listed in the above numerical range are also applicable.
[0008] Molybdenum powder and potassium bicarbonate are mixed and ball-milled under an inert atmosphere. During the ball-milling process, the molybdenum powder and potassium bicarbonate are evenly mixed and a partial solid solution effect is produced to prepare a mixed powder; the present invention uses potassium carbonate as a potassium source and directly adds it to achieve the effect of pore formation and dispersion, while when other potassium sources such as potassium carbonate are used, it is necessary to add them in batches to achieve the effect of first pore formation and then dispersion, and the operation steps are complicated. If the potassium source is potassium hydroxide, it can also decompose to produce gas, but its product is oxygen, which is flammable and explosive when mixed with hydrogen, and has low safety. If potassium bicarbonate is replaced with sodium bicarbonate, the solubility of sodium in water in the subsequent reaction is lower than that of potassium, the dispersion efficiency is low, and sodium is additionally introduced to the molybdenum powder, which affects the subsequent screening and sintering performance, while potassium is an important element that is beneficial to improving the screening and sintering activity of molybdenum powder.
[0009] Under a reducing atmosphere, the mixed powder is subjected to a first heat preservation treatment at the decomposition temperature of potassium bicarbonate. During the heat preservation process, the potassium bicarbonate in the mixed powder is decomposed to produce potassium carbonate and gas, and the gas is used to form pores. Then the temperature is raised to 1000°C~1150°C for a second heat preservation treatment. During the heat preservation process, potassium carbonate is decomposed to produce potassium oxide, and potassium oxide reacts with water vapor to produce liquid potassium hydroxide. Under the action of liquid potassium hydroxide, the dispersion of molybdenum powder is promoted to obtain monodisperse porous molybdenum powder.
[0010] For example, the temperature of the second heat preservation treatment is 1000° C., 1050° C., 1100° C., 1150° C., etc., but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0011] Specifically, the decomposition temperature of potassium bicarbonate is 180°C. During the first heat preservation treatment, the potassium bicarbonate in the mixed powder decomposes to produce gas and potassium carbonate, and the produced water vapor and carbon dioxide gas are used to form pores. During the second heat preservation treatment, the potassium carbonate further decomposes to produce potassium oxide, and the potassium oxide and water vapor react to generate liquid potassium hydroxide, so that the nano-particle molybdenum powder adheres to each other, thereby making the particle size of the molybdenum powder uniform, promoting the dispersion of the molybdenum powder, and obtaining monodisperse porous molybdenum powder.
[0012] In a preferred embodiment of the present invention, during the reduction treatment, the reduction time is 4 h to 6 h, for example, the reduction time is 4 h, 5 h, 6 h, etc., but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0013] In a preferred embodiment of the present invention, the amount of potassium bicarbonate added is 10% to 40% of the mass of the molybdenum powder. For example, the amount of potassium bicarbonate added is 10%, 20%, 30%, 40%, etc., of the mass of the molybdenum powder, but is not limited to the listed values. Other values not listed within the above numerical range are also applicable.
[0014] In a preferred embodiment of the present invention, in the second insulation treatment, the heating rate is 50°C / min. Before the second insulation treatment, the temperature needs to be quickly increased to reach the temperature required for the second insulation treatment. The purpose is to avoid the complete decomposition of potassium bicarbonate during the heating process, which affects the effect of the subsequent second insulation treatment.
[0015] In a preferred embodiment of the present invention, the ball milling time is 30h~50h, and the ball milling speed is 50r / min~200r / min. For example, the ball milling time is 30h, 35h, 40h, 45h, 50h, etc., and the ball milling speed is 50r / min, 100r / min, 150r / min, 200r / min, etc., but it is not limited to the listed values, and other values not listed in the above numerical range are also applicable.
[0016] In a preferred embodiment of the present invention, in the first heat preservation treatment, the heat preservation time is 10 minutes.
[0017] In a preferred embodiment of the present invention, in the second heat preservation treatment, the heat preservation time is 15 minutes to 30 minutes. For example, the heat preservation time is 15 minutes, 20 minutes, 25 minutes, 30 minutes, etc., but it is not limited to the listed values, and other values not listed in the above numerical range are also applicable.
[0018] In a preferred embodiment of the present invention, the reducing atmosphere in the reduction treatment is hydrogen.
[0019] The reducing atmosphere in the first and second heat-retaining treatments is hydrogen.
[0020] The inert atmosphere was argon.
[0021] The second object of the present invention is to provide monodisperse porous molybdenum powder prepared by the above preparation method.
[0022] The third object of the present invention is to provide the use of the above-mentioned monodisperse porous molybdenum powder in preparing a coating.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] After lamellar molybdenum dioxide is reduced at 750°C~800°C to obtain small-particle molybdenum powder, it is mixed with potassium bicarbonate by ball milling. After a low-temperature reaction at the decomposition temperature of potassium bicarbonate to increase the porosity, the temperature is raised to 1000°C~1150°C. The liquid potassium hydroxide makes the nano-particle molybdenum powder adhere to each other, thereby making the particle size of the molybdenum powder uniform, promoting the dispersion of the molybdenum powder, and obtaining monodisperse porous molybdenum powder.
[0025] The monodisperse porous molybdenum powder prepared by the present invention has a particle size of 1-4 μm and a specific surface area of 4 m 2 / g~6m2 / g, the porosity is 50%~70%, and the monodisperse porous molybdenum powder is sprayed on the ceramic green body by cold spraying. When the thickness is 0.95mm, the bonding strength with the ceramic matrix can reach 34.2MPa~40.3MPa. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a scanning electron microscope image of the monodisperse porous molybdenum powder prepared in Example 1 of the present invention.
[0027] Figure 2 This is a scanning electron microscope image of the monodisperse porous molybdenum powder prepared in Example 2 of the present invention.
[0028] Figure 3 This is a scanning electron microscope image of the monodisperse porous molybdenum powder prepared in Example 3 of the present invention.
[0029] Figure 4 This is a scanning electron microscope image of the monodisperse porous molybdenum powder prepared in Comparative Example 1 of the present invention.
[0030] Figure 5 This is a scanning electron microscope image of the monodisperse porous molybdenum powder prepared in Example 4 of the present invention.
[0031] Figure 6 This is a scanning electron microscope image of the monodisperse porous molybdenum powder prepared in Example 5 of the present invention.
[0032] Figure 7 This is a scanning electron microscope image of the monodisperse porous molybdenum powder prepared in Example 6 of the present invention.
[0033] Figure 8 This is a scanning electron microscope image of the monodisperse porous molybdenum powder prepared in Comparative Example 2 of the present invention.
[0034] Fig. 9 This is a scanning electron microscope image of the monodisperse porous molybdenum powder prepared in Comparative Example 3 of the present invention. DETAILED DESCRIPTION
[0035] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] MoO used in the present invention 2 The powder has a particle size of 10 μm and a lamellar morphology.
[0037] Example 1
[0038] Step 1: In a hydrogen atmosphere, 20 g of lamellar MoO 2The powder was reduced with hydrogen at 750°C for 4 h to obtain molybdenum powder.
[0039] Step 2: ball-mill the obtained molybdenum powder and 10% potassium bicarbonate, with argon as the protective atmosphere, a ball-to-material ratio of 1:4, a rotation speed of 50 r / min, and a ball-milling time of 30 h, to obtain a mixed powder after the ball-milling.
[0040] Step 3: The obtained mixed powder was kept at 180°C in a hydrogen atmosphere for 10 min; then the temperature was rapidly increased to 1000°C at a heating rate of 50°C / min and high-temperature reduced for 15 min to obtain monodisperse porous molybdenum powder. The scanning image is as follows: Figure 1 As shown, the particle size is 3.1 μm.
[0041] The BET test shows that the specific surface area of the monodisperse porous molybdenum powder prepared in Example 1 is 4.1 m 2 / g, porosity is 51.2%.
[0042] Example 2
[0043] Step 1: 20g of lamellar MoO 2 The powder was first reduced with hydrogen at 765°C for 6 h to obtain molybdenum powder.
[0044] Step 2: ball-mill the obtained molybdenum powder and 10% potassium bicarbonate, with argon as the protective atmosphere, a ball-to-material ratio of 1:4, a rotation speed of 200 r / min, and a ball-milling time of 50 h to obtain a mixed powder after the ball-milling.
[0045] Step 3: The obtained mixed powder was kept at 180°C in a hydrogen atmosphere for 10 min; then the temperature was rapidly increased to 1150°C at a heating rate of 50°C / min and high-temperature reduced for 30 min to obtain a monodisperse porous molybdenum powder. The scanning image is as follows: Figure 2 As shown, the particle size is 2.3 μm.
[0046] The BET test shows that the specific surface area of the monodisperse porous molybdenum powder prepared in Example 2 is 4.9 m 2 / g, porosity is 60.3%.
[0047] Example 3
[0048] Step 1: 20g of lamellar MoO 2 The powder was first reduced with hydrogen at 800°C for 6 h to obtain molybdenum powder.
[0049] Step 2: ball-mill the obtained molybdenum powder and 10% potassium bicarbonate, with argon as the protective atmosphere, a ball-to-material ratio of 1:4, a rotation speed of 200 r / min, and a ball-milling time of 50 h to obtain a mixed powder after the ball-milling.
[0050] Step 3: The obtained mixed powder was kept at 180°C in a hydrogen atmosphere for 10 min; then the temperature was rapidly increased to 1150°C at a heating rate of 50°C / min and high-temperature reduced for 30 min to obtain a monodisperse porous molybdenum powder. The scanning image is as follows: Figure 3 As shown, the particle size is 2.3 μm.
[0051] The BET test shows that the specific surface area of the monodisperse porous molybdenum powder prepared in Example 3 is 5.6 m 2 / g, porosity is 68.2%.
[0052] Comparative Example 1
[0053] Step 1: In a hydrogen atmosphere, 20 g of lamellar MoO 2 The powder was reduced with hydrogen at 700°C for 4 h to obtain molybdenum powder.
[0054] Step 2: ball-mill the obtained molybdenum powder and 5% potassium bicarbonate, with argon as the protective atmosphere, a ball-to-material ratio of 1:4, a rotation speed of 50 r / min, and a ball-milling time of 30 h to obtain a mixed powder after the ball-milling.
[0055] Step 3: The obtained mixed powder was kept at 180°C in a hydrogen atmosphere for 10 min; then the temperature was rapidly increased to 1000°C at a heating rate of 50°C / min and high-temperature reduced for 15 min to obtain molybdenum powder. The scanning image is as follows: Figure 4 As shown, the particle size is 5.6 μm.
[0056] The BET test shows that the specific surface area of the molybdenum powder prepared in Comparative Example 1 is 4.9 m 2 / g, and the porosity is 55.4%. When the potassium bicarbonate content is too low, the decomposition cannot produce enough gas, and the porosity of the molybdenum powder decreases.
[0057] Example 4
[0058] Step 1: 20g of lamellar MoO 2 The powder was first reduced with hydrogen at 765°C for 4 h to obtain molybdenum powder.
[0059] Step 2: ball-mill the obtained molybdenum powder and 40% potassium bicarbonate, with argon as the protective atmosphere, a ball-to-material ratio of 1:4, a rotation speed of 50 r / min, and a ball-milling time of 30 h to obtain a mixed powder after the ball-milling.
[0060] Step 3: The obtained powder was kept at 180°C in a hydrogen atmosphere for 10 min; then the temperature was rapidly increased to 1000°C at a heating rate of 50°C / min and high-temperature reduced for 15 min to obtain monodisperse porous molybdenum powder. The scanning image is as follows: Figure 5 As shown, the particle size is 3.8 μm.
[0061] The BET test shows that the specific surface area of the monodisperse porous molybdenum powder prepared in Example 4 is 4.7 m 2 / g, porosity is 60.2%.
[0062] Example 5
[0063] Step 1: 20g of lamellar MoO 2 The powder was first reduced with hydrogen at 800°C for 6 h to obtain molybdenum powder.
[0064] Step 2: ball-mill the obtained molybdenum powder and 40% potassium bicarbonate, with argon as the protective atmosphere, a ball-to-material ratio of 1:4, a rotation speed of 200 r / min, and a ball-milling time of 50 h to obtain a mixed powder after the ball-milling.
[0065] Step 3: The obtained mixed powder was kept at 180°C in a hydrogen atmosphere for 10 min, and then rapidly heated to 1150°C at a heating rate of 50°C / min and subjected to high-temperature reduction for 30 min to obtain monodisperse porous molybdenum powder. The scanning image is as follows: Figure 6 As shown, the particle size is 2.8 μm.
[0066] The BET test shows that the specific surface area of the monodisperse porous molybdenum powder prepared in Example 5 is 4.9 m 2 / g, porosity is 64.9%.
[0067] Example 6
[0068] Step 1: 20g of lamellar MoO 2 The powder was first reduced with hydrogen at 800°C for 6 h to obtain molybdenum powder.
[0069] Step 2: ball-mill the obtained molybdenum powder and 40% potassium bicarbonate, with argon as the protective atmosphere, a ball-to-material ratio of 1:4, a rotation speed of 200 r / min, and a ball-milling time of 50 h to obtain a mixed powder after the ball-milling.
[0070] Step 3: The obtained mixed powder was kept at 180°C in a hydrogen atmosphere for 10 min, and then rapidly heated to 1150°C at a heating rate of 50°C / min and subjected to high-temperature reduction for 30 min to obtain monodisperse porous molybdenum powder. The scanning image is as follows: Figure 7 As shown, the particle size is 2.8 μm.
[0071] The BET test shows that the specific surface area of the monodisperse porous molybdenum powder prepared in Example 7 is 5.1 m 2 / g, porosity is 69.7%.
[0072] Comparative Example 2
[0073] Step 1: In a hydrogen atmosphere, 20 g of lamellar MoO 2The powder was reduced with hydrogen at 750°C for 4 h to obtain molybdenum powder.
[0074] Step 2: ball-mill the obtained molybdenum powder and 50% potassium bicarbonate, with argon as the protective atmosphere, a ball-to-material ratio of 1:4, a rotation speed of 50 r / min, and a ball-milling time of 30 h to obtain a mixed powder after the ball-milling.
[0075] Step 3: The obtained mixed powder is kept at 180°C in a hydrogen atmosphere for 10 minutes; then the temperature is rapidly increased to 1000°C at a heating rate of 50°C / min and high-temperature reduced for 15 minutes to obtain molybdenum powder. Figure 8 As shown, the particle size is 6.9 μm and there are large-sized agglomerated particles. This is because the further increase of potassium bicarbonate content leads to an increase in potassium hydroxide content, and nano-molybdenum powders aggregate with each other in a large range, reducing the dispersibility.
[0076] The BET test shows that the specific surface area of the molybdenum powder prepared in Comparative Example 2 is 3.2 m 2 / g, porosity is 5.8%.
[0077] Comparative Example 3
[0078] Step 1: In a hydrogen atmosphere, 20 g of lamellar MoO 2 The powder was reduced with hydrogen at 750°C for 4 h to obtain molybdenum powder.
[0079] Step 2: ball-mill the obtained molybdenum powder and 5% potassium bicarbonate, with argon as the protective atmosphere, a ball-to-material ratio of 1:4, a rotation speed of 50 r / min, and a ball-milling time of 30 h to obtain a mixed powder after the ball-milling.
[0080] Step 3: The obtained mixed powder was kept at 180°C in a hydrogen atmosphere for 10 min; then the temperature was raised to 1000°C at a heating rate of 5°C / min and high-temperature reduced for 15 min to obtain molybdenum powder. The scanning image is as follows: Fig. 9 As shown, the particle size is 7.3 μm.
[0081] The BET test shows that the specific surface area of the molybdenum powder prepared in Comparative Example 3 is 2.4 m 2 / g, porosity is 15.6%.
[0082] Application Example 1
[0083] The monodisperse porous molybdenum powder prepared in Example 1 was sprayed on the alumina ceramic green body by cold spraying, with a spraying distance of 110 mm and a spraying speed of 0.3 m. 3 / min, the spraying angle was 90°, the argon flow rate was 40.5nlpm, and the mixture was cooled naturally to obtain an alumina ceramic green body containing molybdenum powder with a spraying thickness of 0.95mm.
[0084] The alumina ceramic green body containing molybdenum powder is sintered at 1600° C. for 3 hours to obtain the alumina ceramic containing molybdenum powder.
[0085] The bonding strength between molybdenum powder and alumina ceramics in alumina ceramics containing molybdenum powder was tested by a tensile test method, and the bonding strength was measured to be 34.6 MPa.
[0086] Application Example 2
[0087] The monodisperse porous molybdenum powder prepared in Example 2 was sprayed on the alumina ceramic green body by cold spraying. The spraying distance was 20 mm, the spraying speed was 50 mm / s, the spraying angle was 90°, the temperature was 400°C, the pressure was 3.0 MPa, and the powder feeding flow rate was 30 g / min to obtain an alumina ceramic green body containing molybdenum powder with a spraying thickness of 0.95 mm.
[0088] The alumina ceramic green body containing molybdenum powder is sintered at 1600° C. for 3 hours to obtain the alumina ceramic containing molybdenum powder.
[0089] The bonding strength between molybdenum powder and alumina ceramics in alumina ceramics containing molybdenum powder was tested by a tensile test, and the bonding strength was measured to be 36.5 MPa.
[0090] Application Example 3
[0091] The monodisperse porous molybdenum powder prepared in Example 3 was sprayed on the alumina ceramic green body by cold spraying. The spraying distance was 20 mm, the spraying speed was 50 mm / s, the spraying angle was 90°, the temperature was 400°C, the pressure was 3.0 MPa, and the powder feeding flow rate was 30 g / min to obtain an alumina ceramic green body containing molybdenum powder with a spraying thickness of 0.95 mm.
[0092] The alumina ceramic green body containing molybdenum powder is sintered at 1600° C. for 3 hours to obtain the alumina ceramic containing molybdenum powder.
[0093] The bonding strength between molybdenum powder and alumina ceramics in alumina ceramics containing molybdenum powder was tested by a tensile test, and the bonding strength was measured to be 38.7 MPa.
[0094] Application Comparative Example 1
[0095] The monodisperse porous molybdenum powder prepared in Comparative Example 1 was sprayed on the alumina ceramic green body by cold spraying. The spraying distance was 20 mm, the spraying speed was 50 mm / s, the spraying angle was 90°, the temperature was 400°C, the pressure was 3.0 MPa, and the powder feeding flow rate was 30 g / min to obtain an alumina ceramic green body containing molybdenum powder with a spraying thickness of 0.95 mm.
[0096] The alumina ceramic green body containing molybdenum powder is sintered at 1600° C. for 3 hours to obtain the alumina ceramic containing molybdenum powder.
[0097] The bonding strength between molybdenum powder and alumina ceramics in alumina ceramics containing molybdenum powder was tested by a tensile test, and the bonding strength was measured to be 18.9 MPa.
[0098] Application Example 4
[0099] The monodisperse porous molybdenum powder prepared in Example 4 was sprayed on the alumina ceramic green body by cold spraying. The spraying distance was 20 mm, the spraying speed was 50 mm / s, the spraying angle was 90°, the temperature was 400°C, the pressure was 3.0 MPa, and the powder feeding flow rate was 30 g / min to obtain an alumina ceramic green body containing molybdenum powder with a spraying thickness of 0.95 mm.
[0100] The alumina ceramic green body containing molybdenum powder is sintered at 1600° C. for 3 hours to obtain the alumina ceramic containing molybdenum powder.
[0101] The bonding strength between molybdenum powder and alumina ceramics in alumina ceramics containing molybdenum powder was tested by a tensile test, and the bonding strength was measured to be 36.4 MPa.
[0102] Application Example 5
[0103] The monodisperse porous molybdenum powder prepared in Example 5 was sprayed on the alumina ceramic green body by cold spraying. The spraying distance was 20 mm, the spraying speed was 50 mm / s, the angle was 90°, the temperature was 400°C, the pressure was 3.0 MPa, and the powder feeding flow rate was 30 g / min to obtain an alumina ceramic green body containing molybdenum powder with a spraying thickness of 0.95 mm.
[0104] The alumina ceramic green body containing molybdenum powder is sintered at 1600° C. for 3 hours to obtain the alumina ceramic containing molybdenum powder.
[0105] The bonding strength between molybdenum powder and alumina ceramics in alumina ceramics containing molybdenum powder was tested by a tensile test, and the bonding strength was measured to be 37.8 MPa.
[0106] Application Example 6
[0107] The monodisperse porous molybdenum powder prepared in Example 6 was sprayed on the alumina ceramic green body by cold spraying. The spraying distance was 20 mm, the spraying speed was 50 mm / s, the angle was 90°, the temperature was 400°C, the pressure was 3.0 MPa, and the powder feeding flow rate was 30 g / min to obtain an alumina ceramic green body containing molybdenum powder with a spraying thickness of 0.95 mm.
[0108] The alumina ceramic green body containing molybdenum powder is sintered at 1600° C. for 3 hours to obtain the alumina ceramic containing molybdenum powder.
[0109] The bonding strength between molybdenum powder and alumina ceramics in alumina ceramics containing molybdenum powder was tested by a tensile test, and the bonding strength was measured to be 39.1 MPa.
[0110] Application Comparative Example 2
[0111] The monodisperse porous molybdenum powder prepared in Comparative Example 2 was sprayed on the alumina ceramic green body by cold spraying. The spraying distance was 20 mm, the spraying speed was 50 mm / s, the angle was 90°, the temperature was 400°C, the pressure was 3.0 MPa, and the powder feeding flow rate was 30 g / min to obtain an alumina ceramic green body containing molybdenum powder with a spraying thickness of 0.95 mm.
[0112] The alumina ceramic green body containing molybdenum powder is sintered at 1600° C. for 3 hours to obtain the alumina ceramic containing molybdenum powder.
[0113] The bonding strength between molybdenum powder and alumina ceramics in alumina ceramics containing molybdenum powder was tested by a tensile test, and the bonding strength was measured to be 10.3 MPa.
[0114] Application Comparative Example 3
[0115] The monodisperse porous molybdenum powder prepared in Comparative Example 3 was sprayed on the alumina ceramic green body by cold spraying. The spraying distance was 20 mm, the spraying speed was 50 mm / s, the angle was 90°, the temperature was 400°C, the pressure was 3.0 MPa, and the powder feeding flow rate was 30 g / min to obtain an alumina ceramic green body containing molybdenum powder with a spraying thickness of 0.95 mm.
[0116] The alumina ceramic green body containing molybdenum powder is sintered at 1600° C. for 3 hours to obtain the alumina ceramic containing molybdenum powder.
[0117] The bonding strength between molybdenum powder and alumina ceramics in alumina ceramics containing molybdenum powder was tested by a tensile test, and the bonding strength was measured to be 17.6 MPa.
[0118] Monodisperse porous molybdenum powder has a large number of pores and specific surface area, which increases the contact area between the molybdenum powder and the substrate. Because it is corroded by the liquid potassium hydroxide generated in the second insulation process, it has a certain roughness, which improves the bonding strength. The internal stress generated during cold spraying and sintering can also be absorbed by sufficient pores, and the uniform particle size also avoids the appearance of small grains, effectively improving the bonding strength with ceramics.
[0119] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0120] Obviously, those skilled in the art may make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A method for preparing monodisperse porous molybdenum powder, characterized in that: The following steps are involved: Under a reducing atmosphere, the lamellar molybdenum dioxide is subjected to a reduction treatment at 750°C to 800°C to obtain molybdenum powder; Molybdenum powder and potassium bicarbonate are mixed and ball-milled in an inert atmosphere to obtain a mixed powder; the amount of potassium bicarbonate added is 10% to 40% of the mass of the molybdenum powder; Under a reducing atmosphere, the mixed powder is subjected to a first heat preservation treatment at the decomposition temperature of potassium bicarbonate. During the heat preservation process, the potassium bicarbonate in the mixed powder is decomposed to produce potassium carbonate and gas, and the gas is used to form pores. Then the temperature is raised to 1000°C~1150°C for a second heat preservation treatment. During the heat preservation process, potassium carbonate is decomposed to produce potassium oxide, and potassium oxide reacts with water vapor to produce liquid potassium hydroxide. Under the action of liquid potassium hydroxide, the dispersion of molybdenum powder is promoted to obtain monodisperse porous molybdenum powder.
2. The method for preparing a monodisperse porous molybdenum powder according to claim 1, characterized in that: During the reduction treatment, the reduction time is 4h~6h.
3. The method for preparing a monodisperse porous molybdenum powder according to claim 1, characterized in that: In the second heat preservation treatment, the heating rate was 50° C. / min.
4. The method for preparing a monodisperse porous molybdenum powder according to claim 1, characterized in that: The ball milling time is 30h~50h, and the ball milling speed is 50r / min~200r / min.
5. The method for preparing a monodisperse porous molybdenum powder according to claim 1, characterized in that: In the first heat preservation treatment, the heat preservation time is 10 minutes.
6. The method for preparing a monodisperse porous molybdenum powder according to claim 1, characterized in that: In the second heat preservation treatment, the heat preservation time is 15min~30min.
7. The method for preparing a monodisperse porous molybdenum powder according to claim 1, characterized in that: The reducing atmosphere in the reduction treatment is hydrogen; The reducing atmosphere in the first heat preservation treatment and the second heat preservation treatment is hydrogen; The inert atmosphere was argon.
8. A monodisperse porous molybdenum powder prepared by the preparation method according to any one of claims 1 to 7.
9. Use of the monodisperse porous molybdenum powder according to claim 8 in preparing a coating.
Citation Information
Patent Citations
Method for preparing porous molybdenum metal by adopting powder metallurgy method
CN101988162A
Preparation method of graphene having porous structure
CN103449414A